Nodular Liver in Portosinusoidal Vascular Disease: A Case of Mistaken Identity. Issue 3 (May 2022) - Alkashash, Ahmad M.; Khan, Shahbaz; Nephew, Lauren; Kubal, Chandrashekhar A.; Nelson, Nick; Saxena, Romil
Abstract : Background: Portosinusoidal vascular disease (PSVD) has been proposed as a unifying term for vascular abnormalities of the small portal veins and sinusoids that occur in the noncirrhotic liver. This term supersedes other designations including incomplete septal cirrhosis, nodular regenerative hyperplasia, hepatoportal sclerosis, and obliterative portal venopathy. Most patients have noncirrhotic portal hypertension, but the latter is not required to establish a diagnosis of PSVD. Diagnosis requires a liver biopsy of adequate size (≥20 mm long) in the presence of accompanying clinical signs of noncirrhotic portal hypertension and/or histological changes of PSVD. We report a case of severe PSVD that caused severe liver atrophy and required transplantation for intractable hepatic encephalopathy. The explanted liver showed numerous focal nodular hyperplasia-like nodules. Case Report: A 57-year-old man with neurofibromatosis type 2 and diabetes mellitus type 2 controlled with insulin developed ascites and signs of portal hypertension. He was presumed to have cirrhosis due to nonalcoholic fatty liver disease and underwent liver transplantation for intractable portal hypertension and severe hepatic encephalopathy. The explanted liver had a nodular appearance; however, histological sections showed no bridging fibrosis. Thin, incomplete curvilinear fibrous septa were seen emanating from portal tracts in a patchy distribution. Our case illustrates that PSVD may cause severe hepatic atrophy and lead to architectural abnormalities that may radiologically mimic the parenchymal nodularity of cirrhosis.